Effect of NaOH Treated Oil Palm Empty Fruit Bunch (OPEFB) on Adsorption of Cd (II) Under Acidic Condition - Hafizah, Naihi; Rubiyah, Baini; Ibrahim, Yakub (Science Research Society, 2021)
Adsorption is an effective way of extracting heavy metal ions from aqueous solutions. Alkali treatment is a chemical modification method that is influenced by concentration and time. The study aims to investigate the effect of NaOH treatment of OPEFB on Cd (II) adsorption under acidic condition. The alkali treatment was done by varying the concentration of NaOH (0.1 M, 0.5 M, and 1.0 M) and the immersion time (12 h and 24 h). SEM images confirmed the existence of pores on the treated OPEFB in comparison with the raw OPEFB. Characterization of treated adsorbent using FTIR resulted in a change of functional groups peak’s position such as hydroxyl and carboxyl groups after the alkali treatment, which might involve Cd (II) adsorption. OPEFB treated with 1.0 M NaOH and 24 h immersion time showed the highest Cd (II) removal under acidic condition (pH 4). All the NaOH treated OPEFB showed an increment in adsorption efficiencies compared to raw OPEFB, suggesting that this treated biomass has a potential for application as an adsorbent for the removal of Cd (II) from wastewater